An AIE fluorescent switch with multi-stimuli responsive properties and applications for quantitatively detecting pH value, sulfite anion and hydrostatic pressure. (28th January 2019) - Lin, Tingting; Su, Xing; Wang, Kai; Li, Minjie; Guo, Hongwei; Liu, Lulu; Zou, Bo; Zhang, Yu-Mo; Liu, Yifei; Zhang, Sean Xiao-An
Abstract : An AIE fluorescent switch exhibited multi-parameter detection properties for pH, sulfite anion and pressure with good linear relationships. Abstract : Stimuli-responsive fluorescent materials which can change their optical signal outputs upon changes in ambient physical or chemical parameters exhibit great application potential for comprehensive environmental monitoring. In this article, a new aggregation-induced emission fluorescent switch, 1', 3′, 3′-trimethyl-5′-(4-(1, 2, 2-triphenylvinyl)phenyl)spiro[chromene-2, 2′-indoline]-6-carbonitrile (TPE-Sp-CN ), was synthesized and applied in the quantitative detection of three parameters, namely pH value, sulfite anion and hydrostatic pressure, with different molecular states. According to the analysis of the optical spectra, TPE-Sp-CN can distinguish water pH values from 0 to 4, the detection limit of sulfite anion is 1.04 ppm, and the pressure sensing range is 1 atm to 6 GPa with the sensing sensitivity of a 9.876 nm GPa −1 shift in the PL spectrum. Furthermore, TPE-Sp-CN can quantitatively sense all three parameters with good linear relationships, which is rarely reported. Also, it is promising to useTPE-Sp-CN as an indicator to monitor the environment or disasters that are related to the above parameters, such as harmful geological activities.